Scale invariant Einstein–Cartan theory in three dimensions - Adak, Muzaffer; Özdemir, Neşe; Sert, Özcan (Springer Science and Business Media LLC, 2023)
AbstractWe retreat the well-known Einstein–Cartan theory by slightly modifying the covariant derivative of spinor field by investigating double cover of the Lorentz group. We first write the Lagrangian consisting of the Einstein–Hilbert term, Dirac term and a scalar field term in a non-Riemannian spacetime with curvature and torsion. Then by solving the affine connection analytically we reformulate the theory in the Riemannian spacetime in a self-consistent way. Finally we discuss our results and give future perspectives on the subject.
Keywords: QB460-466; Nuclear and particle physics. Atomic energy. Radioactivity; FOS: Physical sciences; QC770-798; General Relativity and Quantum Cosmology (gr-qc); Astrophysics; General Relativity and Quantum Cosmology